Electric field modulations of band alignments in arsenene/Ca(OH)2 heterobilayers for multi-functional device applications. (18th September 2017) - Xia, Congxin; Xiong, Wenqi; Du, Juan; Peng, Yuting; Wei, Zhongming; Li, Jingbo
Abstract: van der Waals heterobilayers have been considered to be an ideal option to enhance the electronic properties of original two-dimensional (2D) materials. We predicate theoretically that the 2D arsenene/Ca(OH)2 heterobilayers possess the characteristics of the indirect gap of 2.28 eV and type-I band alignment. Moreover, the electric field can induce the indirect–direct band gap transition of arsenene/Ca(OH)2 heterobilayers. Interestingly, the band alignment transition from type-I to type-II and type-III can be also tailored using the strength and direction of the electric field. These results provide the possibility of realizing the 2D materials-based multi-functional optoelectronic devices by applying electrostatic gating.